Weltersia obscura, a new slug from the island of Montecristo (Tuscan Archipelago, Italy): a hitherto undiscovered endemic or a recent alien? (Mollusca, Pulmonata, Limacidae). Issue 7 (3rd October 2021) - Giusti, Folco; Lesicki, Andrzej; Benocci, Andrea; Pieńkowska, Joanna R.; Manganelli, Giuseppe
Abstract : Unexpectedly, an unknown limacid slug was found in damp meadows and granite trails on the western side of Montecristo, a small island of the Tuscan Archipelago (N Tyrrhenian Sea, Italy), the malacofauna of which has been extensively studied in the last 50 years. It is distinguished from all other anatomically studied limacid species: its duct of the bursa copulatrix joins to the female distal genitalia while in all other limacids except Limacus flavus, it joins to the penis (or the genital atrium). Several other features distinguish the Montecristo slug from L. flavus : body colour, structure of ovispermiduct and free oviduct (with a peculiar sphincter in the new slug), internal structure of the penis and female distal genitalia. Analysis of the nucleotide sequences of several mitochondrial (COI, 16S rDNA) and nuclear (ITS2, 28S rDNA) gene fragments supported the assignation of the Montecristo slug to the family Limacidae, but also its distinction from all molecularly characterized species from the genera Limax, Ambigolimax, Bielzia, Lehmannia, Limacus and Malacolimax . Therefore we decided to describe it within a new genus as Weltersia obscura sp. nov. The origin of this slug is obscure – it is not clear if it is an endemic species overlooked in previous field studies or an alien species introduced to the island very recently. http://zoobank.org/urn:lsid:zoobank.org:act:0C5A2CC2-A94D-4B1D-8DF9-04FA54374E93 : http://zoobank.org/urn:lsid:zoobank.org:act:0C6E4F69-E3E3-494F-BC1E-F7F49E9B529F